Evaluation of Corroded OPS Fiber-Concrete using NDT Method - Zaki, Ahmad; P Rosyidi, Sri Atmaja; Kencanawati, Ni Nyoman; Fonna, Syarizal; Ibrahim, Zainah; Khalid, Hammad R; Al-Osta, Mohammed A (International Journal of Integrated Engineering, 2024)
Concrete is one part of an infrastructure that is very commonly used, materials widely used in making concrete, such as sand and gravel, come from nature that are limited and will run out if used continuously. Oil palm shell (OPS) waste is an alternative that can be used to solve this problem. In this study the proportion of OPS used was 0%, 25%, 50%, and 75% as a partial substitute for coarse aggregate. Pre- and post-corrosion specimens use beam sizes with dimensions of 10 cm × 10 cm × 50 cm. The specimen has a corrosion rate of 7%. The specimen is tested for flexural strength, in addition, the specimen is tested using the Non-Destructive Testing (NDT) method at the age of 28 days and after acceleration corrosion. The NDT method is one way for early inspection to determine the condition of a concrete structure. The NDT methods used in this study were resistivity and impact-echo as evaluation tools for the influence of OPS and fiber on corroded concrete. Based on the results that have been carried out, the lowest resistivity value was 10.87 kohm/cm on 0% OPS post-corrosion specimen and the highest resistivity value of 24.12 kohm/cm on 0% OPS pre-corrosion specimen. Meanwhile, the impact-echo test obtained the lowest value of 2625.33 kHz on 75% OPS post-corrosion specimen and the highest impact-echo value of 11725.26 kHz on 0% OPS post-corrosion specimens. With the increase in the percentage of OPS, the resistivity obtained in pre-corrosion concrete will decrease as well as the impact echo value, except for the 75% OPS specimen, while in post-corrosion specimen impact-echo and resistivity are inversely proportional. The greater the percentage of OPS in concrete, the resistivity value tends to increase but the frequency of impact-echo tends to decrease except specimen with 75% OPS.